Formulation of Nutrient-Enriched Wheat-Based Cookies Using Defatted Soybean Flour and Moringa stenopetala Leaf Powder - Melat Bereket Sherif; Debebe Worku Dadi; Neela Satheesh; Henock Woldemichael Woldemariam (Journal of Food Quality)
Cookies, despite their popularity among both children and adults and being regarded as one of the most functional baked products, often have lower nutritional value due to their primary ingredient, wheat. Therefore, this research aimed to improve the nutritional value of wheat-based cookies using Moringa (Moringa stenopetala) leaf powder (MLP) and defatted soybean flour (DSF) and optimize the blending ratio, baking time, and temperature. From preliminary tests, the blending ratios were ranged from 65% to 85%, 1% to 20%, and 5% to 15% for wheat, DSF, and MLP, respectively, whereas the baking temperature and time were ranged from 180°C to 200°C and 7–11 min, respectively. The result showed that there were significant differences (p<0.05) among the formulated samples in nutritional and functional characteristics at different blending ratios, baking temperatures, and baking times. It was also found that the optimum parameters to develop functional cookies in terms of the optimum overall acceptability, protein content, and TPC were when the blending ratio of 75% wheat, 15% DSF, and 10% MLP, with baking temperature at 180°C for 8.75 min. The cookies developed using these optimum parameters had a protein content and TPC of 15.54% and 2.64 mg GAE/g, respectively, with the overall acceptability score of 6.49 (on a seven-point hedonic scale). In addition, the optimized cookies had 16.76%, 3.82%, 9.10%, 1.96%, 57.12%, and 424.23 kcal/100 g of crude fat, fiber, moisture, ash, carbohydrate, and calories, respectively. In addition, the antioxidant activities of the optimized cookies with the percentage of inhibition were 39.81% for DPPH and 35% for FRAP. These cookie samples also had the values of 6.40 N for hardness, 0.29 for water activity, and 5.14% for spread ratio. The findings of this study showed that the blending ratio of the three ingredients had a significant impact on the sensorial acceptability of the developed cookies, as well as protein content and TPC were highly influenced by DSF and MLP ratios. Therefore, developing nutrition-enriched wheat-based cookies by blending with defatted soybean and M. stenopetala leaf powder using the aforementioned optimum parameters will improve the nutritional content of the cookies product with the preferred overall sensorial acceptability.